Environmental, social, governance risk versus cooperation models between financial institutions and businesses. Sectoral approach and ESG risk analysis - Zioło, Magdalena; Bąk, Iwona; Cheba, Katarzyna; Filipiak, Beata Zofia; Spoz, Anna (Frontiers in Environmental Science, 2023)
ESG risk and business sector matters in the process of adapting business models towards sustainability. Financial institutions play a crucial role in financing the transition of sustainable business models. However, their impact is different depending on the business sector and model of the financial system (bank or market oriented). The study assumes that the financial system model determines the form of cooperation between financial institutions and companies in the process of financing costs towards sustainability. Also, the ways to achieve sustainability in companies' business models differ from business sectors. The article aims to analyze ESG risk, taking into account the business sectors most affected by ESG risk, and to identify the relationship between ESG risk and cooperation models of financial institutions and companies (Anglo-Saxon/German-Japanese). The original research approach was based on including the model of the financial system in the analysis of ESG risk impact and the companies' way of achieving sustainable business models with external funding. The paper is based on a two-stage analysis. First, fuzzy cognitive maps are used to evaluate the strength and direction of the relations occurring between the factors included in the companies' sustainable business models according to the business sectors. In the second stage, correspondence analysis was carried out to distinguish four groups of companies' industries characterized by homogenous features related to the business sector, sustainable business model (SBM), and the way to transform to sustainability. Finally, the cooperation's "financial institution – company" model and recommendations were proposed.